Characterizing Viewpoints of Scholars in Agricultural Communications as they Relate to Research Themes in the Journal of Applied Communications: A Q Methodological Study - Jean A Parrella; Jessica R Spence; Tobin Redwine; Holli R Leggette (Journal of Applied Communications, 2021)
Research in agricultural communications is not guided by a national research agenda. Therefore, the substantial body of research produced from scholars working in the discipline represents scattered efforts. We conducted a content analysis of journal articles published in the Journal of Applied Communications between 2000 and 2019 to identify the research themes that establish the discipline’s scholarly base. Through an examination of n = 259 journal articles, we identified N = 27 research themes, the most prevalent of which included agriculture and media relations/practices (f = 30; % = 11.58), public perceptions/understanding of agriculture and natural resources (f = 25; % = 9.65), and agricultural communications academic programs and curricula (f = 21; % = 8.11). Then, we used Q methodology to identify viewpoints of agricultural communications scholars (e.g., faculty, graduate students; n = 45) as they relate to perceptions about the importance of research. We identified four dominant viewpoints of scholars in agricultural communications: Message Framing Influencers, Extension-Focused Scholars and Practitioners, Discipline-Conscious Researchers, and Tech-Savvy Scholars. Together, these viewpoints explained 59.43% of the study variance. Although participants who represented each of these groups had unique perspectives, participants generally agreed that public perceptions/understanding of agriculture and natural resources and crisis communications in agricultural communications were important research themes. Likewise, they generally agreed that the role of agricultural communications professional organizations, agricultural communications efforts during historical events, and agritourism were not important research themes.
Keywords: content analysis; research agenda; research themes; Q methodology; Q sort